Science And Faith Conflict: Fact Or Fiction? - Espiritu, Wilson Angelo G (Archīum Ateneo, 2017)
" I believe in science but not in religion" is a perspective that is becoming widespread among “Millennials” especially those who join the atheistic, agnostic, and freethinkers bandwagon. They view the relationship of faith and science as adversarial and that alliance with only one of them is imperative if one is to be reasonable. Thus the prevailing misconception: A person of science cannot be a person of faith and a person of faith cannot be a person of science. This article intends to address this issue. It argues that this conflict between faith and science originates from a certain erroneous understanding of the relationship between the two. Pointing out the problems that lead to the conflict thesis, namely scientific fundamentalism and ecclesiastical authoritarianism, this paper proposes that faith and science could well relate with each other by delineating their differences and autonomy while recognizing the possibility and necessity of dialogue and collaboration. It could then be upheld that to acknowledge the reliability of scientific truths does not necessarily entail the abandonment of religious faith and vice versa.